COMPARISON OF VIDEO CALL INSTRUCTIONS AND VOICE CALLS IN INDONESIAN LANGUAGE ON CHEST COMPRESSION ONLY HAND POSITION - Maulidah; Virdiyanti, Ruri; Wahid, Abdurahman; Rahmawati, Emelia (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Out of Hospital Cardiac Arrest (OHCA) or cardiac arrest events that occur outside the hospital are the focus of world health problems which is often threaten a person's life. First aid that must be given quickly and precisely is Cardio Pulmonary Resuscitation (CPR). The rapid initiation of CPR with correct hand positioning by laypersons in cases of OHCA is critical for improving survival rates. Objectives: The purpose of this study was to compare the accuracy of the hand position of the lay rescuer when performing chest compressions only which was instructed through video calls and voice calls in Indonesian Language. Methods: This research was an experimental study. Sampling using probability sampling. The sample consists of 40 people who were divided into 2 groups, namely the instruction group via video call and voice call. Results: The results show that in the video call group there were as many as 9 people (45%) who performed hand placement during CPR correctly, while in the voice call group there were 13 people (65%). The statistical results using Mann Whitney test showed that there was no significant difference between video call and voice calls instructions in Language (p = 0.209). Conclusion: It needs the training for Emergency Medical Services (EMS) operator officers prior to conducting the study and the near real situations as the original incident in order to get more effective on performing chest compressions.